An innovative approach to teaching and learning about the nature of science: student’s learning outcomes / Beh Kian Lim. - Beh, Kian Lim (Universiti Teknologi MARA Cawangan Selangor, 2011)
This paper is based on the author’s classroom experience. It looks into the content and the methodology used in the classroom for SCE500- Nature of Science (NOS), a course for pre-service science teachers. It highlights the innovative and creative elements of the class lessons especially pertaining to the variety of approaches used in the set induction of every class session. These approaches were based on the consensus model of the Nature of Science. Among the approaches were using optical illusions as illustrations of what constitutes observation and the notion that observation is theory laden, using the developmental model of the atom from the historical perspective as illustration for the tentativeness of scientific ideas, using ‘ magnetic field’ as revealed by dusting iron filings around a bar magnet to illuminate the notion that scientific constructs are created by scientists, using specific examples of scientific law and theory in conceptualising the distinction between theory and law in view of the misconceptions harboured by students that theory with sufficient evidence will become law, and, using the duality of light as particles and waves to illustrate the possibility of multiple theories for a particular set of data. The paper also highlights the eight misconceptions of NOS commonly found among students and the effectiveness of the course in addressing these misconceptions based on students’ course feedback and the quantitative data obtained before and after the course using an inventory designed by the author to gauge students’ conceptual gain in the eight aspects of NOS.